Small Bowel Obstructions Caused by Barbed Sutures in Robotic Surgery: A Systematic Review - Renata Pajtak; Krinal Mori (Reproductive Medicine, 2025)
Background/Objectives: Barbed sutures have been recognised to offer numerous advantages compared to traditional sutures in minimally invasive procedures including holding tension. However, they are also associated with increased reports of small bowel obstructions (SBOs) in laparoscopic procedures. We are the first to conduct a review on the incidence of SBOs secondary to the use of barbed sutures in robotic surgery. Our aim is to raise awareness about this rare complication and promote early recognition and timely intervention, leading to a reduction in the incidence of severe complications and thereby improving patient outcomes. Methods: A systematic review of the literature was performed by searching the Ovoid Medline, PubMed and Cochrane Databases. After applying our exclusion criteria of articles unavailable in English, seven articles remained. We examined the literature and calculated the median and mean ranges for surgical procedures, time to presentation, symptoms of presentation, type of complications involving the bowel, the type of barbed suture and the additional length of hospital stay. Results: Our systematic review revealed eight cases of bowel obstruction secondary to the use of a barbed suture during robotic surgery. Robotic sacrocolpopexy had the highest complication rate: the median time to presentation was 14 days with vomiting being the most common presenting symptom. Most cases were resolved with a diagnostic laparoscopy and truncation of the barbed suture, and length of re-admission was a median of 4 days. Discussion: The introduction of new devices always carries advantages as well as unfortunate complications. Minimisation of complications through learnt surgical techniques including shortening thread tails and prompt recognition of the complication on re-presentation are key to optimising future patient care. Conclusions: Further prospective trials in this field will be useful to assess the appropriate use of the barbed suture as well as research dedicated to exploring alternate adhesive sutures.